Fiscal Resilience Building : Insights from a New Tax Revenue Diversification Index - Ouedraogo, Rasmane (IMF Working Papers; Working Paper ;, 2020)
Does the reliance on diversified tax structure enhance resilience to fiscal risks? This paper gives an answer to this question by proposing a new cross-country tax revenue diversification index (RDI). The RDI builds on the Theil index, and unlike the few existing tax diversification indices, which are constructed only at the state level for the US, is computed at the national level, covering a broad panel of 127 countries over the period 2000-15. We find suggestive evidence that tax revenue diversification reduces tax revenue volatility, thus bringing to the data long-held views about the prominence of tax revenue diversification for fiscal resilience strengthening. While exploring the drivers of the RDI, we find that tax revenue diversification is not just a reflection of economic diversification, but also an outcome of macroeconomic, political and institutional factors. Interestingly, a non-monotone relationship is also at play between the RDI and economic development, with countries' portfolio of tax sources getting more diversified as their economy develops, until a tipping point, where richer countries start finding it harder to diversify further their tax revenue sources.